Social relationships, modes of communication and gratitude expression (2020)
This study analyses the possible association between gratitude expression, state of gratitude, different modes of computer mediated communication and how they are mediated by the relationship between benefactor and beneficiary. 88 college students answered an online questionnaire in which they benefited from 3 hypothetical helping behaviors. Following the study's design, the responses were analyzed using repeated measures anovas and chi-square tests. The findings from the study indicate a significant effect of the social relationship between benefactor and beneficiary on gratitude, the expression of gratitud and mode of communication chosen to express gratitude. Thus demonstrating that gratitude state, gratitude expression and mode of communication are dependent on factors such as the proximity and role-based nature of relationships between benefactors and beneficiaries.